Changing trends in cesarean section: from 1950 to 2020 - Patel, Babulal S.; Kedia, Noopur; Shah, Sushma R.; Agrawal, Saumya P.; Patel, Vismay B.; Patel, Adwait B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Caesarean section (C.S) is a part of the standard care in modern obstetrics. The indications for a caesarean section as an alternative to vaginal delivery have evolved over the centuries. Its practicality, disponibility, and apparent safety have placed caesarean section, a first-line procedure in many clinical scenarios. The awareness of perinatal mortality and morbidity associated with safety of caesarean, expert anaesthesia, potent antibiotics, blood transfusion facilities and better neonatal care have increased incidence of caesarean section very fast. Thus, there is fast, steady and definite rise in incidence of caesarean section everywhere. But the question is ‘Is a rising caesarean section rate is inevitable?’. Studies carried out to understand CS deliveries has adopted different framework. The issue treats elements of ethics in the medical profession, gender issues, choices of women, the quality of institutional services, etc. The findings of retrospective studies have suggested that the caesarean section rate could be reduced in certain categories. In this study, we discuss the various ways in which it can be achieved.